Early Mobilization and Functional Discharge Criteria Affecting Length of Stay after Total Elbow Arthroplasty - Prkič, A; Viveen, J; The, B; Koenraadt, K. L. M; Eygendaal, D (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2020)
PURPOSE OF THE STUDY Decline in length of stay is of growing interest for patients, doctors and health insurances. The aim of our study was to assess the safety and length of stay after omission of casting, start of early mobilization and implementation of functional discharge criteria after total elbow arthroplasty (TEA). MATERIAL AND METHODS We retrospectively reviewed all patients' records who received a Coonrad-Morrey TEA in the period from January 1st, 2011 to December 31st, 2018. From these records, indications, demographic information and complications were derived. Length of stay was calculated from the hospital administration. Patients were divided in three groups to evaluate the two changes in post-operative care. RESULTS In total 125 patients receiving 126 Coonrad-Morrey TEAs were included with a mean length of stay of 5.5 days (range 2- 23) for the entire group. Omitting a post-operative cast led to decline in length of stay from 6.2 to 5.4 days (p < 0.001). Introduction of functional discharge criteria in August 2017 declined mean length of stay to 3.8 days (p < 0.001). The surgical technique (triceps-on versus triceps-off) was not a confounder (p = 0.20). Range of motion after one year was not significantly different between groups. DISCUSSION The length of stay declined after omission of a cast, and declined further after introducing functional discharge criteria. Since no higher complication rates were observed, the shortening of length of stay appears to be safe. This is in line with other fast-track programs, i.e. for hip and knee arthroplasty. The surgical technique used were not a confounder for the shortened length of stay, which further adds to the safety of the functional discharge criteria. CONCLUSIONS Omitting a cast and splint as regular post-operative treatment reduced the length of stay significantly without leading to more complications. Introduction of functional discharge criteria lowered the length of stay further without more complications. Key words: fast track rehabilitation, cast, total elbow arthroplasty, length of stay, discharge, complications.
Keywords: časné pohybování; Length of Stay; urychlená pooperační rehabilitace; Early Ambulation; totální endoprotéza loketního kloubu; Retrospective Studies; Arthroplasty, Replacement, Elbow; retrospektivní studie; lidé; Patient Discharge; Postoperative Complications; pooperační komplikace; Humans; Enhanced Recovery After Surgery; propuštění pacienta; délka pobytu